Pentingnya Penelitian Tindakan Kelas Bagi Guru dalam Pembelajaran - Anisatul Azizah (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2021)
Classroom action research is scientific activity that done by the teacher in the classroom that use actions to improve the quality of learning. Beside, classroom action research also helps teacher to improve their profesionalism. Classroom action research very important for teacher, because doing the reasearh can solve learning problem that will helpimprove the quality of education in Indonesia.therefore, researchers will discuss about the urgency of doing classroom action research. Keywords: Classroom action research, teacher, urgency.